Inorganic oxide hollow particles

Inorganic oxide hollow particles with a specific structure and composition reduce dielectric loss, enhancing signal transmission in electronic devices by providing a lower dielectric loss.

JP7624888B2Active Publication Date: 2025-01-31TAIHEIYO CEMENT CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021107838
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-29
Filing Date
2021-06-29
Publication Date
2025-01-31
Estimated Expiration
2041-06-29

AI Technical Summary

Technical Problem

Existing inorganic oxide particles used in printed wiring boards have high dielectric loss, which hinders the transmission of large-capacity digital signals at high speeds in electronic devices.

Method used

Inorganic oxide hollow particles with a specific structure, comprising multiple independent cavities covered by an outer shell, containing specific amounts of boron, calcium, and aluminum oxides, and having a high hollow ratio and aspherical shape, to reduce dielectric loss.

Benefits of technology

The inorganic oxide hollow particles achieve a lower dielectric loss, enabling faster and more efficient transmission of digital signals in electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624888000002
    Figure 0007624888000002
  • Figure 0007624888000003
    Figure 0007624888000003
  • Figure 0007624888000001
    Figure 0007624888000001
Patent Text Reader

Abstract

To provide an inorganic oxide hollow particle having its relative dielectric constant reduced compared to the conventional art.SOLUTION: An inorganic oxide hollow particle has a plurality of independent spaces in which an outer shell-covered cavity is divided by one or more partitions. The particle comprises an inorganic oxide comprising 10 mass% or more and 40 mass% or less of boron oxide, 5 mass% or less of group 1 element oxide, 5 mass% or more and 50 mass% or less of calcium oxide, and less than 14 mass% of aluminum oxide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to inorganic oxide hollow particles. [Background technology]

[0002] Since inorganic oxide hollow particles have cavities surrounded by an outer shell, they are lighter in weight, have lower thermal conductivity, and are superior in thermal stability compared to non-hollow particles, and are therefore widely used as heat insulating materials, heat shielding materials, catalyst carriers, building materials, electronic materials, etc.

[0003] The inorganic oxide hollow particles are, for example, silica-based hollow particles made from natural vitreous rocks such as perlite and obsidian, with the internal space separated by partitions, and have a density of 0.15 to 0.35 g / cm. 3 Hollow silica particles having a shell thickness of 0.5 to 5 μm at its thinnest part are known (Patent Document 1). 2 / g of hollow silica particles aggregated and bonded together to form a spherical shape. Silica particles (Patent Document 2) and silica-containing hollow particles having a shell (outer shell) containing silica and having nanoparticles of metal and / or metal compound encapsulated in the shell (Patent Document 3) have also been reported. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-172863 A [Patent Document 2] JP 2009-114010 A [Patent Document 3] JP 2016-150880 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, with the remarkable progress of information network technology and the expansion of services utilizing information networks, electronic devices are capable of carrying larger amounts of information and processing faster. In order to transmit large volumes of digital signals at high speeds, it is important to reduce the transmission loss of the printed wiring boards of electronic devices, and inorganic oxide hollow particles used in printed wiring boards are required to have a lower relative dielectric constant. An object of the present invention is to provide inorganic oxide hollow particles having a lower relative dielectric constant than conventional particles. [Means for solving the problem]

[0006] The present inventors conducted research in light of the above problems and found that inorganic oxide hollow particles containing a specific amount of a specific inorganic oxide and having a specific structure can reduce the relative dielectric constant compared to conventional particles.

[0007] That is, the present invention provides the following [1] to [7]. [1] A cavity covered by an outer shell has multiple independent spaces separated by one or more partitions; The inorganic oxide composition includes 10% by mass or more and 40% by mass or less of boron oxide, 5% by mass or less of Group 1 element oxide, 5% by mass or more and 50% by mass or less of calcium oxide, and less than 14% by mass of aluminum oxide. Inorganic oxide hollow particles. [2] The inorganic oxide hollow particles according to [1] above, having a void ratio of 55% or more. [3] The inorganic oxide hollow particles according to [1] or [2] above, which are non-spherical. [4] The inorganic oxide hollow particles according to any one of the above [1] to [3], wherein the shell is non-porous. [5] The inorganic oxide hollow particles according to any one of the above [1] to [4], further comprising 20% ​​by mass or more and 70% by mass or less of silicon oxide as the inorganic oxide. [6] The inorganic oxide hollow particles according to any one of the above [1] to [5], which have an average particle size of 10 μm or less. [7] The inorganic oxide hollow particles according to any one of the above [1] to [6], having a film thickness of 50 nm or more and 1 μm or less. Effect of the Invention

[0008] According to the present invention, it is possible to provide inorganic oxide hollow particles having a lower relative dielectric constant than conventional ones. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a scanning electron microscope (SEM) image of the inorganic oxide hollow particles obtained in Example 1. [Diagram 2] 1 is a sketch of a cross section of the inorganic oxide hollow particles obtained in Example 1 observed with a scanning electron microscope (SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In this specification, "hollow particles" refers to particles having a cavity inside the outer shell. As shown in Figs. 1 and 2, the inorganic oxide hollow particles of the present invention have a cavity covered by the outer shell, which has a plurality of independent spaces separated by one or more partition walls, and each independent space is formed by bubbles (hereinafter also referred to as "independent bubbles") that are not connected to each other and are separated by partition walls. In this specification, the "outer shell" refers to a wall located on the most surface side of the particle and contacting only one independent bubble inside the particle. The "partition wall" refers to a wall that separates two adjacent independent bubbles inside the particle from each other. In addition, since the inorganic oxide hollow particles of the present invention have no openings in the outer shell and are non-porous, the independent bubbles are completely closed. Since the inorganic oxide hollow particles of the present invention have such independent bubbles and are non-porous, they not only have a low relative dielectric constant but also exhibit excellent heat insulation and heat shielding properties, and the particle strength is further increased by the multiple partition walls of the independent bubbles. Furthermore, from the viewpoint of lowering the relative dielectric constant, the inorganic oxide hollow particles of the present invention are preferably non-aggregated primary particles. The absence of pores in the shell can be confirmed by scanning electron microscope (SEM) images or by floating on water. Therefore, the inorganic oxide hollow particles of the present invention are different from porous particles having multiple pores extending from the particle surface to the inside. In addition, it is possible to clearly distinguish them from porous particles and secondary particles by scanning electron microscope (SEM) images.

[0011] In this specification, the content of each inorganic oxide described below is a value obtained by measuring in oxide equivalent by X-ray fluorescence analysis and calculating the chemical component. Each chemical component is calculated by correcting according to the following formula so that the total value of the oxides of the element to be analyzed is 100%. For example, ZSX primus II (manufactured by Rigaku Corporation) can be used as the X-ray fluorescence analyzer.

[0012] Chemical composition (after correction) (%) = Chemical composition (before correction) × 100 / (100-impurities (%)) The impurity content (%) is calculated by subtracting the total value of the above-mentioned chemical composition of the oxide from 100.

[0013] The inorganic oxide hollow particles of the present invention have shells and partition walls formed of inorganic oxides including boron oxide, Group 1 element oxide, calcium oxide and aluminum oxide. By forming the shells and partition walls from such inorganic oxides, it is possible to reduce the relative dielectric constant compared to conventional particles.

[0014] As the boron oxide, B2O3 is preferable from the viewpoint of lowering the relative dielectric constant. Examples of the Group 1 element oxide include lithium oxide, sodium oxide, potassium oxide, rubidium oxide, and cesium oxide. Among them, from the viewpoint of lowering the relative dielectric constant, lithium oxide, sodium oxide, and potassium oxide are preferred, lithium oxide and sodium oxide are more preferred, and sodium oxide is even more preferred. As the sodium oxide, from the viewpoint of lowering the relative dielectric constant, Na2O is preferred. The Group 1 element oxide may contain one or more types. As the calcium oxide, CaO is preferable from the viewpoint of lowering the relative dielectric constant. As the aluminum oxide, Al2O3 is preferable from the viewpoint of lowering the relative dielectric constant.

[0015] The content of boron oxide is 10% by mass or more and 40% by mass or less, and from the viewpoint of lowering the relative dielectric constant, it is preferably 11% by mass or more, more preferably 12% by mass or more, even more preferably 13% by mass or more, and is preferably 37.5% by mass or less, more preferably 35% by mass or less, even more preferably 32.5% by mass or less, and even more preferably 30% by mass or less. The content of the Group 1 element oxide is 5% by mass or less, and from the viewpoint of lowering the relative dielectric constant, it is preferably 4.5% by mass or less, more preferably 4% by mass or less, and even more preferably 3.5% by mass or less. The lower limit of the content of the Group 1 element oxide is not particularly limited and may be 0% by mass, but from the viewpoint of appropriately controlling the softening point of the glass component, it is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more. The content of the Group 1 element oxide is the total amount of the Group 1 element oxide, and the above content is also applied when only one type of Group 1 element oxide is contained. The calcium oxide content is 5% by mass or more and 50% by mass or less, and from the viewpoint of lowering the relative dielectric constant, it is preferably 5.1% by mass or more, more preferably 5.2% by mass or more, even more preferably 7% by mass or more, still more preferably 10% by mass or more, even more preferably 13% by mass or more, especially preferably 15% by mass or more, and is preferably 48.5% by mass or less, more preferably 47% by mass or less, and even more preferably 45.5% by mass or less. The aluminum oxide content is less than 14% by mass, and from the viewpoint of lowering the relative dielectric constant, it is preferably 13.5% by mass or less. The lower limit of the aluminum oxide content is not particularly limited and may be 0% by mass, but from the viewpoint of improving strength, it is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more.

[0016] The inorganic oxide hollow particles of the present invention may contain silicon oxide as the inorganic oxide constituting the outer shell and the partition walls. As the silicon oxide, SiO2 is preferable from the viewpoint of lowering the relative dielectric constant. From the viewpoint of lowering the relative dielectric constant, the content of silicon oxide is preferably 20% by mass or more, more preferably 22% by mass or more, even more preferably 24% by mass or more, and is preferably 70% by mass or less, more preferably 65% ​​by mass or less, even more preferably 60% by mass or less, even more preferably 55% by mass or less, and especially preferably less than 50% by mass.

[0017] The inorganic oxide hollow particles of the present invention may further contain an inorganic oxide other than those mentioned above as the inorganic oxide constituting the outer shell and the partition walls, for example, an oxide of a Group 2 element other than calcium oxide and an oxide of a Group 4 element. Examples of the Group 2 element oxide other than calcium oxide include MgO, SrO, BaO, and RaO. Examples of the Group 4 element oxide include TiO2, ZrO2, and HfO2. Among them, it is preferable to contain magnesium oxide (MgO). The content of these inorganic oxides can be appropriately selected within a range that does not impair the effects of the present invention. For example, the content of magnesium oxide is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 6% by mass or less, from the viewpoint of lowering the relative dielectric constant. The lower limit of the content of magnesium oxide is not particularly limited, and may be 0% by mass, but is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more.

[0018] The hollow ratio of the inorganic oxide hollow particles of the present invention is 55% or more, and from the viewpoint of lowering the relative dielectric constant, it is preferably 60% or more, more preferably 65% ​​or more, even more preferably 70% or more, even more preferably 75% or more, and even more preferably 80% or more. The upper limit of the hollow ratio is preferably 95% or less, and even more preferably 90% or less, from the viewpoint of ensuring sufficient strength. Here, in this specification, the "hollow ratio" is a value calculated from the bulk density and true density of the particles measured using a dry automatic density meter, using the following formula. Since it is difficult to measure each particle, it is the hollow ratio as a particle group. In addition, the "true density" is measured by heating the particles in a box-type electric furnace at a temperature above the melting point for 6 hours in order to remove the hollow parts, cooling them, and measuring them with a dry automatic density meter. As the dry automatic density meter, for example, Accupyc (Shimadzu Corporation) can be used.

[0019] Hollow ratio = (true density - bulk density) x 100 / true density

[0020] Since the inorganic oxide hollow particles of the present invention are minute particles, they can be easily applied to electronic device parts that require miniaturization and thinning. More specifically, the average particle size of the inorganic oxide hollow particles of the present invention is usually 10 μm or less, preferably 8.5 μm or less, more preferably 7.0 μm or less, and even more preferably 6.5 μm or less. From the viewpoint of ensuring sufficient cavities, the lower limit of the average particle size is preferably 0.6 μm or more, more preferably 0.7 μm or more, and even more preferably 0.8 μm or more. Here, in this specification, the "average particle size" refers to the particle size (D) corresponding to 50% of the cumulative distribution curve when the particle size distribution of a sample is prepared on a volume basis in accordance with JIS R 1629. 50 For example, a laser diffraction / scattering type particle size distribution measuring device can be used for measuring the particle size distribution.

[0021] The thickness of the inorganic oxide hollow particles of the present invention is preferably 50 nm or more and 1 μm or less, more preferably 55 to 750 nm, and even more preferably 60 to 500 nm, from the viewpoint of improving strength and reducing weight. The thickness refers to the average value of the thickness of the outer shell and the thickness of the partition wall of the particle, and is measured by the method described in the examples below. Here, in this specification, the "thickness of the outer shell" refers to the thickness of the wall located on the most surface side of the particle, which is in contact with only one independent bubble inside the particle. In addition, the "thickness of the partition wall" refers to the thickness of the wall that separates two adjacent independent bubbles inside the particle. The inorganic oxide hollow particles of the present invention have a thickness of the outer shell and a thickness of the partition wall that are almost equal, and for example, the ratio of the thickness of the partition wall to the outer shell (partition wall / outer shell) is usually 0.5 to 2.0, and preferably 0.8 to 1.5. By setting the thickness in this manner, not only is it easy to achieve a low relative dielectric constant because the cavities are sufficiently secured, but it is also easy to impart sintering heat during production, so that it can be efficiently produced. The film thickness can be observed and measured using a scanning electron microscope (SEM), specifically, by the method described in the Examples below. As the scanning electron microscope, for example, JSM-7001F (manufactured by JEOL Ltd.) can be used.

[0022] The inorganic oxide hollow particles of the present invention are preferably non-spherical in shape. By making the particles non-spherical, the contact area between the particles is small when the particles are added to a resin or the like, and a further reduction in thermal conductivity can be expected.

[0023] The fact that a particle shape is non-spherical can be determined from the aspect ratio. In this specification, the "aspect ratio" refers to a value calculated by the following method. That is, a photograph of the particle is taken with an optical microscope or a digital camera with a close-up function, and the major axis a and diameter b of 30 randomly selected particles are analyzed using commercially available image analysis software from the optical microscope photograph or the digital camera photograph. Then, the ratio (a / b) of the major axis a to the diameter b of the 30 particles is calculated, and the average value is calculated. Here, the "major axis a" refers to the longest diameter of the particle, and the "diameter b" refers to the diameter in the thickness direction of the particle.

[0024] The aspect ratio of the inorganic oxide hollow particles of the present invention is preferably 1.1 or more, more preferably 1.13 or more, even more preferably 1.16 or more, and even more preferably 1.20 or more, from the viewpoint of lowering the relative dielectric constant and maintaining the strength when added as a filler. The upper limit of the aspect ratio is not particularly limited, but is preferably 2.0 or less, more preferably 1.8 or less, and even more preferably 1.6 or less, from the viewpoint of lowering the relative dielectric constant and dispersibility when mixed as a filler.

[0025] From the viewpoint of improving strength, the 50% residual strength of the hollow particles of the present invention is preferably 3 to 500 MPa, more preferably 5 to 100 MPa, further preferably 10 to 50 MPa, and particularly preferably 12 to 30 MPa. Here, in this specification, the "50% residual strength" refers to a value measured by the powder pressing method described in JP2018-136160A.

[0026] From the viewpoint of lowering the dielectric constant, the inorganic oxide hollow particles of the present invention preferably have a relative dielectric constant of 2.0 or less at 1 GHz, more preferably 1.9 or less, even more preferably 1.8 or less, even more preferably 1.7 or less, and most preferably 1.6 or less. Here, in this specification, the "relative dielectric constant" is measured at 1 GHz under an environment of a temperature of 25°C and a humidity of 60%. The relative dielectric constant can be measured, for example, using a perturbation type cavity resonator (manufactured by KEYCOM).

[0027] The inorganic oxide hollow particles of the present invention can be applied to heat insulating materials, heat shielding materials, catalyst carriers, building materials, electronic materials, etc., but since they are fine particles with a low dielectric constant and high strength, they are useful for electronic materials, particularly wiring circuit boards, semiconductor encapsulants, etc.

[0028] In addition, the inorganic oxide hollow particles of the present invention are very small particles and therefore have excellent dispersibility in a medium. The medium is not particularly limited, but examples thereof include resin, paint, rubber, and solvent, which are likely to provide the effects of the present invention. When a resin is used as the medium, it can be used as a resin composition for forming electronic materials, such as wiring circuit boards and semiconductor encapsulants. The resin is not particularly limited as long as it is generally used in the fields of wiring circuits and semiconductor encapsulants.

[0029] The content of the inorganic oxide hollow particles in the resin composition can be appropriately selected depending on the application, but is usually 1 to 97 mass %, preferably 5 to 60 mass %, and more preferably 15 to 40 mass %.

[0030] The resin composition may be in the form of a varnish in which it is dissolved or dispersed in an organic solvent, and the varnish may be impregnated into a substrate to form a prepreg. The solids (non-volatile content) concentration in the varnish can be appropriately selected depending on the application, but is usually 5 to 80 mass %, and preferably 10 to 70 mass %. The substrate to be impregnated with the varnish is not particularly limited, and examples thereof include inorganic fibers, organic fibers, carbon fibers, etc. The impregnation can be carried out by immersion (dipping) or coating.

[0031] Furthermore, for example, a wiring circuit board can be produced by applying the above-mentioned varnish onto a metal foil-coated substrate, heating and curing the varnish to form a resin layer on the metal foil-coated substrate, and then removing the metal foil by etching to form a conductor pattern. When applying the varnish onto a substrate, any suitable application method can be used, such as spraying, roll coating, rotary coating (spin coating), slit die coating (slit coating), or bar coating.

[0032] The method for mixing the medium and the inorganic oxide hollow particles is not particularly limited, but for example, each component may be sufficiently stirred and mixed uniformly using a mixer or the like, and then kneaded using a mixing roll, an extruder, a kneader, a roll, an extruder, etc. The mixing conditions can be appropriately set depending on the mixing method.

[0033] The method for producing inorganic oxide hollow particles of the present invention is not particularly limited as long as it can produce inorganic oxide hollow particles having the above-mentioned configuration. For example, a method can be mentioned in which a liquid to be sprayed containing a raw material compound is sprayed from a spray device installed in a spray pyrolysis device, and the sprayed droplets (mist) are pyrolyzed.

[0034] Examples of the raw material compound include compounds containing one or more elements selected from boron, group 1 elements, calcium, and aluminum as elements constituting an oxide. Such compounds are not particularly limited as long as they are compounds that dissolve in water, and examples include inorganic salts, organic salts, and alkoxides, which may contain one or more of these. Examples of inorganic salts include nitrates, sulfates, carbonates, hydroxides, and halides. Examples of organic salts include formates, acetates, propionates, oxalates, and citrates. The Group 1 element compound is not particularly limited as long as it is a compound containing a Group 1 element, but examples thereof include lithium-containing compounds, sodium-containing compounds, potassium-containing compounds, rubidium-containing compounds, and cesium-containing oxides. Among them, from the viewpoint of lowering the relative dielectric constant, lithium-containing compounds, sodium-containing compounds, and potassium-containing compounds are preferred, lithium-containing compounds and sodium-containing compounds are more preferred, and sodium-containing compounds are even more preferred. Specific examples of sodium-containing compounds include sodium salts such as sodium chloride, sodium hydroxide, and sodium sulfate. In addition, the same inorganic salts as those of the sodium-containing compounds can be used in the lithium-containing compounds, potassium-containing compounds, rubidium-containing compounds, and cesium-containing oxides. Examples of the boron-containing compound include metaborates such as sodium borate and potassium borate, tetraborates such as sodium tetraborate and potassium tetraborate, pentaborates such as sodium pentaborate and potassium pentaborate, and boric acid. Examples of calcium-containing compounds include calcium salts such as calcium nitrate, calcium chloride, calcium hydroxide, calcium formate, calcium acetate, and calcium propionate. Examples of aluminum-containing compounds include inorganic salts such as aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum phosphate, aluminum hydroxide, aluminum acetate, and aluminum oxalate, and aluminum alkoxides such as aluminum methoxide, aluminum ethoxide, and aluminum isopropoxide. In addition, aluminosilicates, solutions in which aluminum oxide is dispersed in a solvent, and sol solutions of aluminum oxide can also be used as the raw compound solutions. Examples of aluminosilicates include sodium aluminosilicate, potassium aluminosilicate, and calcium aluminosilicate.

[0035] In the present invention, the raw material compounds may further include compounds containing elements other than boron, Group 1 elements, calcium, and aluminum. Such compounds are not particularly limited as long as they are water-soluble metal compounds, and examples thereof include one or more selected from titanium salts, magnesium salts, strontium salts, zinc salts, zirconium salts, barium salts, yttrium salts, aluminosilicates, aluminum alkoxides, and silicate alkoxides. Examples of salts of these metals include inorganic salts, organic salts, and alkoxides. Specific examples of inorganic salts and organic salts are as described above.

[0036] Examples of titanium salts include titanium nitrate, titanium sulfate, and titanium chloride. Examples of magnesium salts include magnesium nitrate, magnesium sulfate, magnesium chloride, magnesium phosphate, and magnesium hydroxide. Examples of strontium salts include strontium acetate and strontium propionate. Examples of zinc salts include zinc nitrate, zinc sulfate, and zinc chloride. Examples of zirconium salts include zirconium oxynitrate and zirconium oxychloride. Examples of barium salts include barium nitrate, barium chloride, and barium hydroxide. Examples of yttrium salts include yttrium nitrate, yttrium sulfate, and yttrium chloride. Examples of silicate alkoxides include tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), tetrapropyl orthosilicate (TPOS), and tetrabutoxysilane. In addition, a solution in which silicon oxide is dispersed in a solvent, or a sol solution of silicon oxide can also be used as the raw compound solution. Among these, it is preferable to include one or more selected from magnesium salts and silicate alkoxides in order to easily enjoy the effects of the present invention.

[0037] Examples of oxides obtainable from these raw material compounds include Group 1 element oxides such as boron oxide, sodium oxide, and lithium oxide, calcium oxide, alumina, magnesium oxide, and silica, as well as composite oxides that combine these oxides.

[0038] The liquid to be sprayed can be prepared by mixing the raw material compounds with water or an organic solvent such as ethanol. The mixing ratio of the raw material compounds may be appropriately adjusted according to the type of the raw material compounds so as to obtain hollow inorganic oxide particles having the above-mentioned composition.

[0039] The concentration of the raw material compounds in the liquid to be sprayed is preferably 0.01 mol / L to 2.0 mol / L, and more preferably 0.1 mol / L to 1.0 mol / L, in terms of the total amount of each element.

[0040] The spray pyrolysis apparatus preferably has a pyrolysis furnace with a vertical cylindrical shape, and the size of the pyrolysis furnace can be appropriately selected depending on the production scale.

[0041] Examples of the spraying device include fluid nozzles such as a two-fluid nozzle, a three-fluid nozzle, and a four-fluid nozzle. Here, the type of the fluid nozzle includes an internal mixing type in which the gas and the raw material solution are mixed inside the nozzle, and an external mixing type in which the gas and the raw material solution are mixed outside the nozzle, and either type can be adopted. As the gas to be supplied to the nozzle, for example, air, nitrogen, argon, or other inert gases can be used. Among them, air is preferable from the viewpoint of economy. Incidentally, one or more spraying devices can be installed.

[0042] The flow rate of the liquid to be sprayed is usually 1 to 100 L / h, preferably 3 to 80 L / h, and more preferably 5 to 60 L / h.

[0043] The droplets sprayed from the spray device are heated by a heater in the pyrolysis furnace to form a film containing an inorganic compound, and the film acts as a starting point for the formation of hollow inorganic oxide particles. The droplet ejection speed is usually 1 to 50 m / s, preferably 5 to 35 m / s, and more preferably 10 to 20 m / s.

[0044] Examples of the heating device include a combustion burner, a hot air heater, and an electric heater. One or more heating devices can be installed. Any of the combustion burners, hot air heaters, and electric heaters that are generally available on the market can be used. The temperature of the heating device is preferably 400 to 1800° C., more preferably 600 to 1500° C., further preferably 700 to 1400° C., and even more preferably 800 to 1200° C. At such a temperature, pyrolysis is sufficient, and the particles are less likely to aggregate when discharged outside the pyrolysis furnace.

[0045] The inorganic oxide hollow particles generated by the thermal decomposition reaction are collected from the downstream side of the thermal decomposition furnace using a powder collection device such as a high-performance cyclone powder collection machine or a bag filter.

[0046] In the present invention, the recovered inorganic oxide hollow particles may be mixed with ethanol by stirring, and the particles may be immersed in ethanol once, after which only the particles floating on the liquid surface may be collected. This makes it possible to obtain highly pure inorganic oxide hollow particles in which the cavities inside the particles have closed bubbles. The amount of ethanol used is usually 5 to 20 times by mass, preferably 10 to 15 times by mass, relative to the inorganic oxide hollow particles. EXAMPLES

[0047] The embodiments of the present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0048] 1. Chemical composition analysis The inorganic oxide hollow particles were pressed into briquettes, which were then measured in terms of oxides using an X-ray fluorescence analyzer (ZSX primus II, Rigaku Corporation) to calculate the chemical components. Each chemical component was calculated by correcting the total value of the oxides of the analyzed elements (SiO2, Al2O3, CaO, MgO, B2O3, Na2O, Li2O) to 100% using the following formula.

[0049] Chemical composition (after correction) (%) = Chemical composition (before correction) × 100 / (100-impurities (%)) (In the formula, the impurity (%) is calculated by subtracting the total value of the above-mentioned chemical composition of the oxide from 100.)

[0050] 2. Analysis of void ratio The bulk density and true density of the particles were measured using an Accupyc (Shimadzu Corporation) as a dry automatic density meter, and calculated using the following formula: Note that the true density was measured by heating the particles at or above the melting point for 6 hours in a box-type electric furnace to remove any voids, then cooling and measuring the true density with the dry automatic density meter.

[0051] Cavity ratio = (true density - bulk true density) × 100 / true density

[0052] 3. Average particle size analysis Using a particle size distribution analyzer (MT3000II, manufactured by Microtrack Bell), a volume-based particle size distribution was created in accordance with JIS R 1629, and the particle diameter (D 50 ) was sought.

[0053] 4. Analysis of the presence or absence of partitions and film thickness The particles were observed with a scanning electron microscope (SEM) to confirm the presence or absence of partition walls, and then the thicknesses of the partition walls and the outer shell were measured by the following method. 0.05 g of a sample was mixed with 9 g of epoxy resin, dried, and solidified, and the cured product was cut and the cross section (10 mm x 5 mm) was polished. The polished cross section was observed with a scanning electron microscope (SEM), and the film thickness was measured by the following method. That is, for 30 randomly collected particles, an SEM image was taken for each particle, three points of the partition walls were randomly extracted from the SEM image, the thickness of the center of each of the three points was measured, and the average value was calculated to determine the thickness of the partition walls of the particle. Similarly, three points of the outer shell were randomly extracted from the SEM image, the thickness of the center of each of the three points was measured, and the average value was calculated to determine the thickness of the outer shell of the particle. After the thicknesses of the partition walls and the outer shell were obtained for 30 particles, the average value was calculated to determine the film thickness. The scanning electron microscope used was JSM-7001F (manufactured by JEOL Ltd.).

[0054] 5. Aspect Ratio Analysis The major axis (a) and diameter (b) of the particles were measured from the scanning electron micrograph obtained above, and the ratio was calculated as a / b. This procedure was performed on 30 randomly selected particles, and the average value was calculated.

[0055] 6. Analysis of relative dielectric constant Measurements were taken at 1 GHz using a perturbation type cavity resonator (manufactured by KEYCOM) in an environment with a temperature of 25°C and a humidity of 60%.

[0056] Example 1 The raw inorganic compound-containing aqueous solution was put into the reaction vessel, and the raw inorganic compound-containing aqueous solution was stirred for 3 hours. The raw inorganic compound-containing aqueous solution was prepared by dissolving calcium nitrate (manufactured by Osaki Kogyo) at 0.019 mol / L, magnesium nitrate (manufactured by Ako Kasei) at 0.024 mol / L, aluminum nitrate (manufactured by Hakko Kagaku Kogyo) at 0.052 mol / L, tetraethyl orthosilicate (manufactured by Tama Kagaku Kogyo) at 0.192 mol / L, and boric acid (manufactured by Yoneyama Kagaku Kogyo) at 0.184 mol / L in tap water. Subsequently, the raw inorganic compound-containing aqueous solution was sent to a two-fluid nozzle, and the raw inorganic compound-containing aqueous solution was sprayed from the nozzle into a spray pyrolysis furnace, and the inorganic oxide hollow particles were recovered by firing at 1100°C. 20 g of the recovered inorganic oxide hollow particles were mixed with 300 g of ethanol and stirred, and the particles were immersed in ethanol once, and only the particles floating on the liquid surface were collected. The collected inorganic oxide hollow particles were then analyzed, and the results are shown in Table 1. The collected inorganic oxide hollow particles and an SEM image of their cross sections are shown in Figure 1, and a sketch of the cross section is shown in Figure 2.

[0057] Examples 2 to 4 and Comparative Example 1 Inorganic oxide hollow particles were collected in the same manner as in Example 1, except that calcium nitrate, magnesium nitrate, aluminum nitrate, tetraethyl orthosilicate, and boric acid were dissolved in tap water to obtain the chemical composition shown in Table 1. The collected inorganic oxide hollow particles were analyzed. The results are shown in Table 1.

[0058] Comparative Example 2 Calcium nitrate, magnesium nitrate, aluminum nitrate, tetraethyl orthosilicate, and boric acid were dissolved in tap water to obtain the chemical composition shown in Table 1, and inorganic oxide hollow particles were produced in the same manner as in Example 1. Then, when a treatment using ethanol was carried out in the same manner as in Example 1, the particles did not float on the liquid surface, so the inorganic oxide particles after production were analyzed. The results are shown in Table 1.

[0059] Comparative Example 3 Inorganic oxide hollow particles were obtained in the same manner as in Example 1, except that calcium nitrate, aluminum nitrate, magnesium nitrate, tetraethyl orthosilicate, and sodium tetraborate were used as raw material compounds and each compound was dissolved in tap water to obtain the chemical composition shown in Table 1. The inorganic oxide hollow particles obtained were analyzed. The results are shown in Table 1.

[0060] Example 5 The raw inorganic compound-containing aqueous solution was put into the reaction vessel, and the raw inorganic compound-containing aqueous solution was stirred for 3 hours. The raw inorganic compound-containing aqueous solution was prepared by dissolving lithium nitrate (Fujifilm Wako Pure Chemical Industries) at 0.012 mol / L, calcium nitrate (Osaki Kogyo Co., Ltd.) at 0.050 mol / L, aluminum nitrate (Hakko Chemical Industries Co., Ltd.) at 0.074 mol / L, tetraethyl orthosilicate (Tama Chemical Industries Co., Ltd.) at 0.223 mol / L, and boric acid (Yoneyama Chemical Industries Co., Ltd.) at 0.295 mol / L in tap water. Then, the raw inorganic compound-containing aqueous solution was sent to a two-fluid nozzle, and the raw inorganic compound-containing aqueous solution was sprayed from the nozzle into a spray pyrolysis furnace, and the inorganic oxide hollow particles were recovered by firing at 1100°C. 20 g of the recovered inorganic oxide hollow particles were mixed with 300 g of ethanol and stirred, and the particles were immersed in ethanol once, and only the particles floating on the liquid surface were collected. The collected inorganic oxide hollow particles were then analyzed, and the results are shown in Table 1.

[0061] [Table 1]

[0062] Comparative Example 1 is a hollow particle having a cavity inside the particle, but since the calcium oxide content is less than 5 mass%, the cavity is not divided by partitions. In addition, since the aspect ratio is 1.06, the particle shape is approximately spherical. It can be seen that the inorganic oxide hollow particle of Comparative Example 1 having such characteristics has a high relative dielectric constant of 3.74. In Comparative Example 2, the calcium oxide content exceeded 50% by mass, which caused the blend balance to be lost, resulting in failure to vitrify and formation of hollow particles. Therefore, analysis of the film thickness and relative dielectric constant was abandoned. In Comparative Example 3, the hollow particles have cavities inside, but the content of the Group 1 element oxide exceeds 5 mass%, so the cavities are not separated by partitions. In addition, since the aspect ratio is 1.07, the particle shape is approximately spherical. It can be seen that the inorganic oxide hollow particles of Comparative Example 3 having such characteristics have a high relative dielectric constant of 2.31. On the other hand, in Examples 1 to 5, since the inorganic oxides contained specific amounts of boron oxide, Group 1 element compounds, and calcium oxide, hollow particles having closed bubbles were obtained. In addition, the inorganic oxide hollow particles of Examples 1 to 5 all had an aspect ratio of 1.20 or more and a non-spherical particle shape. It can be seen that the inorganic oxide hollow particles of Examples 1 to 5 having such characteristics all had a relative dielectric constant of 2.0 or less, which is lower than that of conventional particles. [Explanation of symbols]

[0063] 1. Cross section of inorganic oxide hollow particles 2. Closed bubbles 3. Outer shell 4 Bulkhead

Claims

1. The cavity covered by the outer shell has a plurality of independent spaces separated by one or more partitions, The inorganic oxide composition includes 10% by mass or more and 40% by mass or less of boron oxide, 5% by mass or less of Group 1 element oxide, 5% by mass or more and 50% by mass or less of calcium oxide, and less than 14% by mass of aluminum oxide. Inorganic oxide hollow particles.

2. 2. The inorganic oxide hollow particles according to claim 1, which have a void ratio of 55% or more.

3. 3. The inorganic oxide hollow particle according to claim 1, which is non-spherical.

4. 4. The inorganic oxide hollow particle according to claim 1, wherein the outer shell is non-porous.

5. The inorganic oxide hollow particles according to any one of claims 1 to 4, further comprising 20% ​​by mass or more and 70% by mass or less of silicon oxide as the inorganic oxide.

6. The inorganic oxide hollow particles according to any one of claims 1 to 5, having an average particle size of 10 µm or less.

7. The inorganic oxide hollow particle according to any one of claims 1 to 6, wherein the film thickness is from 50 nm to 1 µm.

Citation Information

Patent Citations

  • JP1974030609A

  • Spherical silica particles and method for producing the same

    JP2009114010A

  • Inorganic hollow carrier and functional material using the carrier

    JP2010172863A

  • Method of producing surface-modified mesoporous silica nanoparticle

    JP2015048297A

  • Inorganic oxide fine hollow particle

    JP2016023095A